(untitled) (CIPEEX, 2025)
Introduction: Sexually transmitted infections (STIs) are a serious public health problem in Brazil, with syphilis standing out. Syphilis is transmitted mainly through sexual contact and vertically from the mother to the fetus, leading to Congenital Syphilis (CS). Objective: This study aims to investigate the prevalence of CS in the municipality of Anápolis from 2013 to 2022. Methodology: This is an observational and cross-sectional analytical study. AArticles were retrieved from the Medline, PubMed, and Virtual Health Library (BVS) databases using the descriptors “Congenital Syphilis”, “Newborn”, “Prenatal”, and “Primary Care”. A literature review was conducted using articles published from 2018 onwards containing the descriptors, excluding those that did not meet these criteria. The data obtained on the prevalence of congenital syphilis and prenatal care for mothers during pregnancy in the municipality of Anápolis from 2013 to 2022 were analyzed in comparison with the existing literature. Results: The study highlights the variability in cases of newborns under 6 days old, indicating differences in prevention and diagnostic efforts.Thus, prenatal care coverage within primary care increased from 2013 to 2022. Conclusion: The increase in syphilis diagnoses in newborns under six days old indicates advances in early detection but reveals the need to improve diagnosis and professional training. Despite the increase in prenatal diagnosis, gaps in follow-up persist, making it essential to strengthen primary care and improve surveillance.